An introduction about synchrotron light for high school teachers - Acioly, Vitor; Santos, Antonio (Education and Development Research, 2024)
This article is motivated by the Sirius School for High School Teachers (ESPEM) and the lack of texts on synchrotron light and its application in basic education. It is aimed at high school teachers of Natural Sciences (Physics, Chemistry and Biology) and aims to present an introduction to the concept of synchrotron radiation, in the largest scientific enterprise in Latin America, the National Center for Research in Energy and Materials (CNPEM), where the newest Brazilian synchrotron light source is located, in a particle accelerator called Sirius. After introducing the reader to the development of Brazilian science, the present work's methodology is to address the conceptual definition and history of synchrotron light, for its understanding in a qualitative way and to generate results that are in dialogue with the application of modern and contemporary physics in basic education, and concluding with the presentation of ideas that dialogue with the content present in school curricula on how to approach these concepts in basic education, which dialogues with the application of Modern and Contemporary Physics in High School.